Perkembangan Pembiayaan Multi Akad di Indonesia: Studi Pendekatan NVivo dan Literatur Review - Doni Yusuf Bagaskara; Rohmadi; Nanik Wahyuni (Universitas Muhammadiyah Jember, 2024)
This study aims to determine the development of multi-contract financing in Indonesia using the NVivo approach. This research uses qualitative methodology with Nvivo approach and literature review.